Nitrogen and phosphorus content in constructed wetlands - Jakubaszek, Anita (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
High effectiveness of organic pollutants and nutrients removal is achieved in biological wastewater treatments plants - in case of proper exploitation of these objects. Nitrogen and phosphorus transformation or removal depends on many physic - chemical and biochemical conditions, deposit and environmental factors. A rule for treating wastewater consists in decomposition of organic compounds included in wastewater in water-soil environment.
Keywords: waste water treatment; constructed wetlands; nitrogen; phosphorus; oczyszczalnia ścieków; oczyszczalnia hydrofitowa; azot; fosfor